Smart Geotechnics for Smart Societies Proceedings of the 17th Asian Regional Conference on Soil Mechanics and Geotechnical Engineering (17th ARC, Astana, Kazakhstan, 14-18 August, 2023) - Zhussupbekov, Askar; Sarsembayeva, Assel; Kaliakin, Victor N. (Taylor & Francis, 2023)
Smart Geotechnics for Smart Societies contains the contributions presented at the 17th Asian Regional Conference on Soil Mechanics and Geotechnical Engineering (17th ARC, Astana, Kazakhstan, 14-18 August, 2023). The topics covered include: Geomaterials for soil improvement Tunneling and rock engineering Slope, embankments and dams Shallow and deep foundations Soil dynamics and geotechnical earthquake engineering Geoenvironmental engineering and frost geotechnics Investigation of foundations of historical structures and monitoring Offshore, harbor geotechnics and GeoEnergy Megaprojects and transportation geotechnics Smart Geotechnics for Smart Societies will be of interest to academics and engineers interested or involved in geotechnical engineering.